Macrophage migration inhibitory factor from nematode parasite as a novel approach to combat obesity and its metabolic complications - Park, Mi-Kyung; Cho, MinKyoung; Yu, Hak Sun (Frontiers in Immunology, 2026)
ObjectiveObesity is a complex chronic disease characterized by excessive fat accumulation, dysregulation of energy homeostasis, and associated mild inflammation, significantly increasing the risk of metabolic diseases, cardiovascular diseases, and other chronic diseases. Addressing this requires innovative approaches targeting the underlying mechanisms. This study investigates the therapeutic effects of Anisakis simplex-derived macrophage migration inhibitory factor (1) on adipogenesis, lipid metabolism, and inflammation in high-fat diet (2)-induced obesity.MethodsWe evaluated the effects of rAs-MIF on adipocyte differentiation, lipid droplet formation, and expression of adipogenic and inflammatory genes in 3T3-L1 cells. In addition, we investigated the effects of orally administered rAs-MIF on lipid accumulation, glucose metabolism, serum biochemical markers, and immune regulation in mice fed a 45% high-fat diet.ResultsrAs-MIF dose-dependently reduced lipid droplet size and triglyceride accumulation, inhibited adipogenesis and inflammatory gene expression, and upregulated adiponectin levels in 3T3-L1 cells. In HFD-fed mice, rAs-MIF decreased body weight gain, fat mass, and serum lipid levels, enhanced glucose tolerance, and activated interscapular brown adipose tissue while suppressing epididymal white adipose tissue lipid synthesis. Moreover, it modulated the immune balance by promoting the polarization of anti-inflammatory macrophages and reducing the production of pro-inflammatory cytokines.ConclusionrAs-MIF demonstrates a dual regulatory effect on adipogenesis and metabolism, highlighting its potential as a therapeutic candidate for obesity.